A gene and drug co-delivery application helps to solve the short life disadvantage of RNA drug. (April 2022) - Li, Mingshan; Ma, Zhongzheng; Peng, Min; Li, Liang; Yin, Meizhen; Yan, Shuo; Shen, Jie
Highlights: SPc co-delivers dsRNA and matrine to form a multicomponent nano-pesticide. Gene silencing of hemocytin leads to severe bacterial infection of aphids. Co-deliver application improves drug's initial acting time and persistence. SPc-mediated co-delivery strategy provides a precedent for drug design. Graphical Abstract: ga1 Abstract: Novel green technology RNA pesticide has been put forward as a promising method for plant protection, but the instability and short life disadvantage of double-stranded RNA (dsRNA) seriously constrain the commercialization process of RNA pesticide. Herein, a star polycation (SPc)-based gene/drug delivery system was constructed for co-delivering hemocytin ( hem ) dsRNA and botanical pesticide matrine to develop a novel multicomponent nano-pesticide for achieving sequential bioactivity against devastating green peach aphids. The self-assembled matrine/SPc complex could be further complexed with dsRNA through electrostatic interaction and hydrogen bond to form nano-sized matrine/SPc/dsRNA complex. The screened ds hem fragment led to efficient gene silencing and high mortality rate through SPc-based topical application, and the main lethal mechanism was through down-regulating hem gene to result in severe bacterial infection. The ds hem fragment was successfully expressed in pET28-BL21 (DE3) RNaseIII - system to prepare matrine/SPc/ds hem complex. Both initial acting time and persistence of matrine/SPc/ds hem complex were remarkably improved in field, which overcame the short life disadvantage of ds hem and slow-acting property of matrine simultaneously. To our knowledge, it is the first success to co-deliver dsRNA and drug by nanoparticle-mediated delivery system in agricultural field.